Pemanfaatan Scirpus Grossus L Sebagai Bahan Tali-Temali Dan Peralatan Rumah Tangga Masyarakat Di Desa Simpang Gunung Tapan Kecamatan Ranah Ampek Hulu Kabupaten Pesisir Selatan Sumatra Barat - Hendra Wijaya, Oziy; Mahyudin, Des (Jurnal Serambi Biologi, 2023)
This study aims to reveal public knowledge about the types of plants that are used to meet the needs of daily life. This research was conducted in Simpang Gunung Tapan village, Ranah Ampek Hulu Tapan village, Pesisir Selatan Regency. This research is an exploratory descriptive research. Data was collected using in-depth interviews, participatory observation, documentation, and literature study. This method is supported by a participatory enobotany assessment technique consisting of open ended interviews, participatory observations with the community as key informants. From the results of the study, it was found that the people of Smpang Gunung Tapan village, Ranah Ampek Hulu Tapan district, Pesisir Selatan Regency still have good knowledge about plant diversity and their use in everyday life. Based on the results of the study, it was found that Scirpus grossus L. is considered a weed in rice fields where it can be controlled manually by plowing or by herbicides. Scirpus grossus L is commonly used to produce mats or bags that have a strong and durable texture but are more inexpensive.